Unifying Conceptual Density Functional and Valence Bond Theory: The Hardness–Softness Conundrum Associated with Protonation Reactions and Uncovering Complementary Reactivity Modes - Stuyver, Thijs (J Am Chem Soc, 2020)
[Image: see text] In this study, we address the long-standing issue—arising prominently from conceptual density functional theory (CDFT)—of the relative importance of electrostatic, i.e., “hard–hard”, versus spin-pairing, i.e., “soft–soft”, interactions in determining regiochemical preferences. We do so from a valence bond (VB) perspective and demonstrate that VB theory readily enables a clear-cut resolution of both of these contributions to the bond formation/breaking process. Our calculations indicate that appropriate local reactivity descriptors can be used to gauge the magnitude of both interactions individually, e.g., Fukui functions or HOMO/LUMO orbitals for the spin-pairing/(frontier) orbital interactions and molecular electrostatic potentials (and/or partial charges) for the electrostatic interactions. In contrast to previous reports, we find that protonation reactions cannot generally be classified as either charge- or frontier orbital-controlled; instead, our results indicate that these two bonding contributions generally interplay in more subtle patterns, only giving the impression of a clear-cut dichotomy. Finally, we demonstrate that important covalent, i.e., spin pairing, reactivity modes can be missed when only a single spin-pairing/orbital interaction descriptor is considered. This study constitutes an important step in the unification of CDFT and VB theory.